Metabolic Engineering of Saccharomyces cerevisiae for High-Level Friedelin via Genetic Manipulation - Gao, Hai-Yun; Zhao, Huan; Hu, Tian-Yuan; Jiang, Zhou-Qian; Xia, Meng; Zhang, Yi-Feng; Lu, Yun; Liu, Yuan; Yin, Yan; Chen, Xiao-Chao; Luo, Yun-Feng; Zhou, Jia-Wei; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Friedelin, the most rearranged pentacyclic triterpene, exhibited remarkable pharmacological activities and anti-insect activity as well. Especially celastrol with friedelin as skeleton, derived from medicinal plant Tripterygium wilfordii, was a promising drug for its anti-cancer and anti-obesity activity. Despite achievement of friedelin production by engineered Saccharomyces cerevisiae in previous study, no strain producing high-level friedelin was stably engineered. In this study, a combined strategy was employed with integration of endogenous pathway genes into genome and knock out of inhibiting gene by CRISPR/Cas9 technology, leading to multiple engineering strains successfully. After introducing an efficient TwOSC1T502E, all strains with genetic integration (tHMG1, ERG1, ERG20 and ERG9) showed 3.0~6.8-fold increase of friedelin production, compared with strain BY4741. Through further double knock-out of inhibiting genes, only strains GD1 and GD3 produced higher-yielding. Moreover, strains GQ1 and GQ3 with quadruple mutant (bts1; rox1; ypl062w; yjl064w) displayed similar increase. Finally, the dominant strain GQ3 with TwOSC1T502E was cultured in an optimized medium in shake flasks, and the final yield of friedelin reached 63.91 ± 2.45 mg/L, which was approximately 65-fold higher than the wide-type strain BY4741 and 229% higher than in ordinary SD-His-Ura medium. It was the highest titer for friedelin production to date. Our work offers a good example for triterpenoids production in microbial cell factories, and lays a solid foundation for the mining, analysis of pathways, and efficient production of those valuable triterpenoids with friedelin as the skeleton.